Polarographic determination of vitamin B1 (tibamine) in pap a ya lea ve juice samples - Khang, Lim Jia (Universiti Sains Malaysia, 2017)
Papaya leaves are commonly used as food and drug that have many medicine claim benefits. Vitamin Bl (thiamine) functions as an important coenzyme for the intermediary metabolism of carbohydrates and some amino acids and a deficiency of it in human is the cause of beriberi. Relatively little quantitative information regarding the existence of thiamine constituent in papaya leaves juice. Hence, this research is concerned with the development of the settings for polarography determination of vitamin B1 in papaya leave juice. The polarography of thiamine has been carried out in aqueous solution in 0.1 M KC1 at pH 5.20 by differential pulse polarography (DPP). The influence of following parameters such as sweep rate, pulse amplitude and pulse time were studied. By using the optimum parameters, thiamine exhibits peak potential fluctuates between -1.15 V to -1.30 V. A calibration based on the different known concentration of standard thiamine, which allows quantification over the range of 0.397 mM to 1.964 mM, was proposed with LOD and LOQ of 0.1273 mM and 0.4244 mM respectively. It was then successfully applied to the determination of thiamine in papaya leave sample. The concentration of thiamine is found to be 7.749 ± 0.999 pg in 100g of normal green leaves (sample 2) and the level is beyond LOQ. Whereas other atypical leaves (sample 1, 3 and 4) found to contain the level of thiamine below LOQ. The observed data for sample 2 (normal green leave) has been subjected to RSD 12.89% which revealed considerably reliability and precision of the method used.